The Short Term Effects of Immigrant Students on the Educational Achievements of Native‐Born Students. (1st February 2016) - Chachashvili‐Bolotin, Svetlana; Lissitsa, Sabina; Shavit, Yossi; Ayalon, Hanna
Abstract: Since 1989 nearly one million immigrants from the FSU have arrived in Israel. Although well‐educated on average, most of these immigrants lacked economic means. The purpose of the present study is to examine whether the presence of immigrants in schools affected the educational achievements of their Israeli‐born peers. We analyzed data pertaining to 8, 288 Israeli tenth graders who attended 208 schools in 1994. Respondents' records were obtained from the Ministry of Education and the Bureau of the Census. Using hierarchical models we examined the effects of the proportion of immigrant students in a school and of their parents' education on the probability that Israeli‐born students in the school would earn matriculation certificates. Results did not yield evidence of any negative spillover effects on the educational achievements of the native students. Moreover, the presence of many immigrant students with high educational backgrounds increased the likelihood of Israeli‐born students earning matriculation certificates.